Analisis Dampak Kehadiran Pasar Modern terhadap Kinerja Pemasaran Pasar Tradisional Berbasis Perspektif Pedagang dan Konsumen di Kabupaten Wonogiri - Wibowo, Frendy; Khasanah, Aulia Uswatun; Putra, Febrianur Ibnu Fitroh Sukono (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2022)
This study aims to analyze the impact of the existence of modern markets on the marketing performance of traditional markets from the perspective of traders and consumers in Wonogiri Regency. This type of research is descriptive qualitative with data collection techniques using interviews. The sampling technique uses non-probability sampling (purposive sampling) with data analysis, organizing data into categories, describing it into units, synthesizing, compiling into patterns, choosing what is important and what will be studied, and drawing conclusions. The results of this study indicate that the presence of modern markets in Wonogiri Regency has positive and negative impacts where traditional market traders do experience a decrease in profits and market share due to segmentation, but traders also feel that with the changing times and regional development it is necessary to adapt and renewal of business systems so as to minimize competition and increase partnerships and competitiveness in the industry. The Government of Wonogiri Regency should be aware of this condition and take a policy in structuring the operating system of the traditional market and modern market, so that it can run more dynamically and side by side without having to have a price war that has a negative impact on the market ecosystem or price stability.